The national minimum wage's effects on the non-wage benefits of labour migrants : evidence from the UK - Elfani, Maria (London Metropolitan University, 2014)
Studies of the minimum wage, particularly of its impact on the labour market, have raised interesting but contentious questions among researchers and policymakers alike. There have been a number of studies which examine the impact of the National Minimum Wage on the UK labour market, but little has been done to examine the effects of the minimum wage on non-wage benefits. There is also a paucity of studies that examine the effects of the minimum wage on migrant workers. This study aims to fill this gap by examining the effects of the minimum wage on the non-wage benefits of migrant workers. Therefore three important and interrelated issues are examined in theoretical and empirical contexts: (i) the effects of the minimum wage on a wide range of non-wage benefits, (ii) the effects of the minimum wage on migration, and (iii) the effects of the minimum wage on the non-wage benefits of migrant workers. It is argued that to some extent the minimum wage has had adverse effects on both non-wage benefits and migrant workers. Primary and secondary research has been conducted by applying mainly positivist quantitative methodology, complemented by a qualitative approach (i.e. a number of interviews) to examine the effects of the minimum wage on the non-wage benefits of migrant workers. The secondary data has been collected from three major labour surveys in the UK: the Annual Survey of Hours and Earnings (ASHE), the Workplace Employee Relations Survey (WERS), and the Labour Force Survey (LFS). The primary data has been collected through a face-to-face questionnaire survey of 200 London-based migrants who have low-paid, low-skilled jobs. The secondary data is analysed using Difference-in-Difference (DID) analysis, while the primary data is analysed through regression analysis, the Pearson’s Chi-squared coefficient, descriptive statistics and qualitative analysis. It is shown through regression that the minimum wage is likely to create adverse effects in the UK labour market, particularly for migrant workers. It was found that the minimum wage has significant negative influences on migrants’ access to numerous valuable non-wage benefits, such as training, holiday pay, paid sick leave and pension schemes. Accommodation/housing, which is a non-wage benefit pertinent to the minimum wage, was also found to be an excuse for not paying statutory wages. Migrants who work in the minimum wage sectors are also less likely to receive health/life insurance. Nevertheless, DID analysis overall shows no evidence that the minimum wage reduces the provision of non-wage benefits. The thesis conclusion addresses the implications of these findings for National Minimum Wage policy, in particular to encourage policymakers to consider the minimum wage’s adverse effects on the UK labour market. The thesis makes some recommendations for National Minimum Wage policy in relation to both non-wage benefits and migrant workers.